Sex-based differences in myocardial infarction-induced kidney damage following cigarette smoking exposure: more renal protection in premenopausal female mice. Issue 6 (23rd June 2020) - Habeichi, Nada J.; Mroueh, Ali; Kaplan, Abdullah; Ghali, Rana; Al-Awassi, Hiam; Tannous, Cynthia; Husari, Ahmad; Jurjus, Abdo; Altara, Raffaele; Booz, George W.; El-Yazbi, Ahmed; Zouein, Fouad A.
Abstract: The impact of cigarette smoking (CS) on kidney homeostasis in the presence of myocardial infarction (MI) in both males and females remains poorly elucidated. C57BL6/J mice were exposed to 2 weeks of CS prior to MI induction followed by 1 week of CS exposure in order to investigate the impact of CS on kidney damage in the presence of MI. Cardiac hemodynamic analysis revealed a significant decrease in ejection fraction (EF) in CS-exposed MI male mice when compared with the relative female subjects, whereas cardiac output (CO) comparably decreased in CS-exposed MI mice of both sexes. Kidney structural alterations, including glomerular retraction, proximal convoluted tubule (PCT) cross-sectional area, and total renal fibrosis were more pronounced in CS-exposed MI male mice when compared with the relative female group. Although renal reactive oxygen species (ROS) generation and glomerular DNA fragmentation significantly increased to the same extent in CS-exposed MI mice of both sexes, alpha-smooth muscle actin (α-SMA) and connective tissue growth factor (CTGF) significantly increased in CS-exposed MI male mice, only. Metabolically, nicotinamide phosphoribosyltransferase (NAMPT) and nicotinamide riboside-1 (NMRK-1) substantially increased in CS-exposed MI female mice only, whereas sirtuin (SIRT)-1 and SIRT-3 substantially decreased in CS-exposed MI male mice compared with their relative female group. Additionally, renal NAD levels significantly decreased only in CS-exposed MI male mice. In conclusion, MI female mice exhibited pronounced renal protection following CS when compared with the relative male groups.